CRISPR genotyping as complementary tool for epidemiological surveillance of Erwinia amylovora outbreaks - Mendes, Rafael (2021)
Fire blight is a destructive plant disease caused by Erwinia amylovora affecting pome fruit trees, and responsible for large yield declines, long phytosanitary confinements, and high economic losses. In Portugal, the first major fire blight outbreaks occurred in 2010 and 2011, and although later considered eradicated, the emergence of other outbreaks in recent years stressed the need to characterize the E. amylovora populations associated with these outbreaks. In this regard, CRISPR genotyping, assessment of three virulence markers, and semi-quantitative virulence bioassays, were carried out to determine the genotype, and assess the virulence of thirty-six E. amylovora isolates associated with outbreaks occurring between 2010 and 2017 and affecting apple and pear orchards located in the country central-west, known as the main producing region of pome fruits in Portugal. The data gathered reveal that 35 E. amylovora isolates belong to one of the widely-distributed CRISPR genotypes (5-24-38 / D-a-α) regardless the host species, year and region. Ea 680 was the single isolate revealing a new CRISPR genotype due to a novel CR2 spacer located closer to the leader sequence and therefore thought to be recently acquired. Regarding pathogenicity, although dot-blot hybridization assays showed the presence of key virulence factors, namely hrpL (T3SS), hrpN (T3E) and amsG from the amylovoran biosynthesis operon in all E. amylovora isolates studied, pathogenicity bioassays on immature pear slices allowed to distinguish four virulence levels, with most of the isolates revealing an intermediate to severe virulence phenotype. Regardless the clonal population structure of the E. amylovora associated to the outbreaks occurring in Portugal between 2010 and 2017, the different virulence phenotypes, suggests that E. amylovora may have been introduced at different instances into the country. This is the first study regarding E. amylovora in Portugal, and it discloses a novel CRISPR genotype for this bacterium.